Perancangan dan Implementasi Aplikasi Web Survei Kepusasan Masyarakat untuk Evaluasi Layanan Publik - Asrorul Faradis; Soffiana Agustin (Jurnal Nasional Komputasi dan Teknologi Informasi, 2026)
Abstrak - Pelayanan publik merupakan indikator penting dalam menilai kualitas tata kelola pemerintahan, sehingga dibutuhkan instrumen evaluasi yang akurat dan mudah diakses. Penelitian ini merancang dan mengimplementasikan aplikasi Survei Kepuasan Masyarakat berbasis web untuk meningkatkan efisiensi pengumpulan dan analisis data layanan publik. Sistem dikembangkan menggunakan metode Waterfall, yang memungkinkan proses pembangunan berjalan sistematis sesuai kebutuhan fungsional. Aplikasi ini dilengkapi fitur formulir survei bertahap, akses melalui QR Code, pengolahan data otomatis, serta visualisasi grafik untuk analisis hasil survei secara real time. Hasil penelitian menunjukkan bahwa sistem ini mampu mengatasi kendala survei konvensional, seperti proses rekap yang lama dan risiko kehilangan data. Selain itu, aksesibilitas yang mudah meningkatkan partisipasi responden, sementara admin dapat memantau tren kepuasan dengan lebih efektif. Secara keseluruhan, aplikasi ini menjadi solusi modern dalam evaluasi layanan publik, mendukung pengambilan keputusan berbasis data, dan meningkatkan kualitas pelayanan secara berkelanjutan. Kata kunci : survei kepuasan; layanan publik; sistem berbasis web; evaluasi digital; sistem informasi; Abstract - Public services are an essential indicator of governance quality, and the increasing demands of citizens for fast, transparent, and accountable services require instruments that can assess service performance accurately. This study presents the design and implementation of a web-based Public Satisfaction Survey System aimed at improving the efficiency and reliability of data collection and evaluation processes in public service institutions. The system was developed using the Waterfall methodology, enabling structured development stages and ensuring that functional requirements were thoroughly addressed. The application integrates several key features, including multi-step survey forms, QR Code access, automated data processing, and graphical visualization to support real-time analysis of survey results. The findings of this study reveal that the developed system successfully overcomes the limitations of conventional surveys, such as data redundancy, lengthy processing time, and potential data loss. Additionally, respondents can easily access the survey across multiple devices, increasing participation rates. Administrators benefit from analytical tools that allow them to monitor satisfaction trends efficiently, which supports decision-making and continuous service improvement. Overall, the web-based survey application proves to be an effective and modern solution for evaluating public services, aligning with the principles of digital transformation in government institutions. The system contributes to transparent, data-driven governance, and improved service quality measurement. Keywords: Prediction; public service; satisfaction survey; web-based system; digital evaluation; information system;